PENGENDALIAN PEDAGANG KAKI LIMA KOTA PAYAKUMBUH (STUDI KASUS : PENGENDALIAN PEDAGANG MALAM JALAN SOEKARNO HATTA/JALAN SUDIRMAN) - Anggraini, Maya; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is motivated because the street vendors in Indonesia is too much and became one of the original contributors of th income for the region in Indonesia. One place that has street vendors and have a characteristic of the city is Payakumbuh. Developed since 1965, the street vendors in Payakumbuh become one of the tourist destinations in this city. The Food street Night is one kinds of street vendor in Payakumbuh which have good attract attention in for all visitors. If the sret vendors or streest food night can not controlles, it can be crowds because they are do their’s job in all of primary road of Payakumbuh city. And then The Government made a laws and Regions No. 9 of 2010 about Street Vendors and/or The Food street Nights for controlles all of the street vendors and /or The Food street Nights activity.This research uses the theory by Siswanto (2011), control is a systematic effort to set performance standards with the goal of planning, designing feedback information system, comparing actual accomplishments with the established standards, determine whether there are irregularities and measure the significance of deviations and take the necessary corrective actions to ensure that all corporate resources are being used wherever possible more efficiently and effectively to the target company.The results of this reseach indicate that control of the street vendors and/or food street night by Market Management Division is less effective. This is evidenced by the absence of the Standard Operating Procedures owned by Market Management Division for implementation of the Regional Regulation Number 9 of 2010. The influence factors is Market Management Division haven’t made the operational procedures standard and no haven’t wrote legitimate and lack of human resources to supervise. Based on these indicators, they really need much resources works with the duties and functions for controlling the vendors and / or food street night Payakumbuh.Keywords: Control, Street Vendors, Food Street nights.